1987
DOI: 10.1557/proc-95-225
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Amorphous and Crystalline Silicon by HR-CVD (Hydrogen Radical Enhanced CVD)

Abstract: Systematic studies have been made on preparation of Si thin films from SiF4 under control over the flow of atomic hydrogens. The gas phase reactions taking place in the mixture of fragments (SiFn) resulting from plasma-induced dissociation and atomic hydrogens were widely investigated by a mass spectroscopy. Chemically active species,i.e., SiF2H and SiH2F were found as those related to the growth of films. The growth in the vicinity of substrates involves either endothermic or radical-enhanced reaction for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…6 Infrared reflectance studies of a-Si:H growth by RMS show that hydrogen can penetrate the surface of the growing film up to a depth of -40 A.•15 The results also indicate that in the sub-surface region there is a dynamic balance between hydrogen incorporation and release during film growth. Such a dynamic process modifies the network structure near the growing surface.…”
Section: Resultsmentioning
confidence: 99%
“…6 Infrared reflectance studies of a-Si:H growth by RMS show that hydrogen can penetrate the surface of the growing film up to a depth of -40 A.•15 The results also indicate that in the sub-surface region there is a dynamic balance between hydrogen incorporation and release during film growth. Such a dynamic process modifies the network structure near the growing surface.…”
Section: Resultsmentioning
confidence: 99%
“…What is the role of excess hydrogen in the plasma? It has been recently (Fujiwara et al, 2000;Shibata et al, 1987) demonstrated that atomic hydrogen can be inserted into strained Si-Si bonds in the subsurface region through the formation of a SiH n complex. Hydrogen dilution should, therefore, result in a more ordered structure; in fact, with increasing hydrogen dilution, one should expect growth of microcrystallites.…”
Section: Glow-discharge Deposition Techniquementioning
confidence: 99%
“…However, to date, few studies have been carried out using chlorinated materials and most studies on amorphous and microcrystalline Si:H (a-Si:H, lc-Si:H) films have been performed by plasma-enhanced chemical vapor deposition (PE-CVD) from SiH 4 [3][4][5]. We have investigated the surface chemistry of H and Cl in the growth of chlorinated hydrogenated amorphous and microcrystalline Si (a-Si:H:Cl, lc-Si:H:Cl) films from SiH 2 Cl 2 , SiHCl 3 , and SiCl 4 , diluted in H 2 using rf PE-CVD.…”
Section: Introductionmentioning
confidence: 99%